Development of a Phase Field Tool Coupling With Thermodynamic Data for Microstructure Evolution Simulation of Alloys in Nuclear Reactors - Guo, Yaolin; Li, Yifan; Liu, Zhen; Shi, Diwei; Song, Jiexi; Zhang, Biao; Bu, Moran; Du, Shiyu (Frontiers in Materials, 2021)
We have developed a new phase field tool PHAFIS to automatically incorporate the thermodynamic data for both of WBM and KKS phase field simulations, which are widely used in the simulation of microstructure evolution of nuclear materials. Based on the generic C/C++ programming language, PHAFIS is capable of automatically parsing the standard TDB files, extracting the free energy and diffusion potential varying with the composition in an analytical way. Based on the two diffrerent TDB files of Fe-Cr binary system and the interpolated data, the phase morphologies during spinodal decomposition at 700 K and liquid-solid transition at high temperatures above 1800 K are reproduced and compared with each other by WBM and KKS model, respectively. Specifically, both of interface-controlled and diffusion-controlled phase transition mechanisms are successfully revealed for solidification through our KKS simulation, consistent with classic phase transition theories. It can be concluded that even slight differences in thermodynamic data will cause significant changes in the microstructure evolution. The integrity of our software tool will facilitate the coupling of phase field methods with thermodynamic data for other materials, paving a fundamental step for coupling more factors required in microstructure simulation.